Effect of remedial teaching on the scholastic performance of children with learning disability - Vincent, Areena C.; Elenjickal, Manju G.; U., Sukumaran T. (International Journal of Contemporary Pediatrics, 2020)
Background: To assess the effectiveness of remedial teaching in children with learning disability and to find association between IQ score and age of the child with their improvement. Methods: An interventional study using pre-post study design, took place in Child Development Centre (CDC) of tertiary care Medical College hospital. Participants includes 45 school going children of age group of 6-15 years. After initial diagnosis and IQ assessment, remedial teaching was given in CDC for 12 months. Techniques are chosen on an individual basis by formulating individualised education program (IEP) by special educators. Diagnosis and pre- post assessment were done using tool, NIMHANS SLD battery. Effectiveness was evaluated as improvement in class levels of students. Definite improvement was decided in each student if improvement was observed in 4 or more domains. Relationship of IQ score and age with their improvement in was noted. Results: In pretest, poor results were found in attention and copying in 39 children, reading in 41, comprehension and spelling in 42, written expression in 43, and arithmetic in 44. In posttest, good results with statistical significance (p<0.05) were found in attention in 33, copying in 27, reading in 24, arithmetic in 15, and spelling in 12 children. Definite improvement was noticed for 33% of students with significant association with age and not IQ score of the child. Conclusions: This study shows that remedial teaching can bring about significant changes in academic skills namely attention, copying, reading, arithmetic, and spelling. 33% had definite improvement in 4 or more domains. The improvement in academic skills following remedial teaching was dependent on the child’s age and not on IQ score.